2013
DOI: 10.1086/670255
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Mass in Spherical Stellar Atmospheres

Abstract: Mass is the most important stellar parameter, but it is not directly observable for a single star. Spherical model stellar atmospheres are explicitly characterized by their luminosity ($L_\star$), mass ($M_\star$) and radius ($R_\star$), and observations can now determine directly $L_\star$ and $R_\star$. We computed spherical model atmospheres for red giants and for red supergiants holding $L_\star$ and $R_\star$ constant at characteristic values for each type of star but varying $M_\star$, and we searched th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This is reassuring and suggests that when applying these corrections, one can ignore the stellar mass. The difference between limb-darkening profiles and angular diameter corrections is small and consistent with previous results by Lester et al (2013).…”
Section: Angular Diameter Correctionssupporting
confidence: 92%
“…This is reassuring and suggests that when applying these corrections, one can ignore the stellar mass. The difference between limb-darkening profiles and angular diameter corrections is small and consistent with previous results by Lester et al (2013).…”
Section: Angular Diameter Correctionssupporting
confidence: 92%
“…When combined with model stellar atmospheres, it is possible to determine the angular diameter where the intensity approaches zero and the optical depth approaches zero (θ τ →0 ) which is designated θ LD (e.g. Lester et al 2013).…”
Section: Indexmentioning
confidence: 99%
“…found that the best-fit limbdarkening angular diameter from interferometric observations do not yield unique measurements of stellar properties. Lester et al (2013) presented a study of CLIV and spectra as a function of stellar mass. If one knows precisely the stellar radius and effective temperature, then the stellar mass can be, at best, measured to a precision of a factor of a few.…”
Section: Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous paper, Lester et al (2013) used the SATLAS (Lester & Neilson 2008) suite of programs to compute spherical stellar atmospheres and synthetic spectra of red giants and red supergiants, which were then searched for indicators of mass. That search concentrated on the visible spectral region, 300-1000nm, because optical interferometry in this region yields the highest angular resolution and also because it has been the traditional range of high-resolution stellar spectroscopy.…”
Section: Introductionmentioning
confidence: 99%